Pembiasaan Jejak Kaki Warna Warni untuk Meningkatkan Kebiasaan Antre Anak Usia Dini - Elidiami, Septiah; Wijaya, Pipit Rika; Triana, Rizki Sevi; Afandi, Ahmad (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to improve the queuing habits of 4–5-year-old children through habituation using visual media in the form of colorful footprints. Queuing is a form of social-emotional development that is essential to instill from an early age to foster discipline, patience, and respect for others. The research method used was Classroom Action Research (CAR) carried out in two cycles. The research subjects were Group A-2 children at TK Al Hidayah 38. Data were collected through observation and documentation. The results showed that the consistent use of colorful footprints as visual media effectively improved children's queuing habits, both when taking stationery and submitting assignments. By the end of the cycles, there was a significant improvement in children's discipline and order during queuing. The data showed that the percentage of children categorized as "developing as expected" and "very well developed" increased from only 17.65% in the pre-cycle to 35.29% in Cycle 1 and 41.17% in Cycle 2. This increase reflects the improved achievement of learning objectives. These findings indicate that habituation using simple visual media can be an effective strategy for fostering positive social behavior in early childhood.